Research on the mechanism of the impact of physical activity on negative emotions of middle school students, and the chain mediating role of social competence and interpersonal relationships - Yining Hu; Liangyu Zhao; Wenze Sui; Yan Gao (Frontiers in Psychology)
BackgroundThis study aims to explore the relationship between physical activity and negative emotions (Depression and anxiety) of high school students and to investigate the mechanisms by which social competence and interpersonal relationships play a role.MethodsA random sampling method was used to select 9,504 students from Shandong Province as the survey subjects. The Physical Activity Questionnaire for Adolescents (PAQ-C), Social Adaptive Behavior Scale (SSBS), Quality of Life Scale for Children and Adolescents (QLSCA), and SCL-90 Symptom Checklist were used to conduct the questionnaire survey.ResultsWe found that (1) Physical activity was significantly positively correlated with social competence and interpersonal relationships (r = 0.122, 0.182, p < 0.01), and significantly negatively correlated with high school students’ negative emotions (r = −0.125, p < 0.01). Social competence, interpersonal relationships, and negative emotions were significantly negatively correlated (r = −0.295 and −0.403, p < 0.01); (2) Social competence and interpersonal relationships partially mediate the relationship between physical activity and high school students’ negative emotions, with mediation effect values of −0.138 and −0.445, respectively; (3) Social competence and interpersonal relationships play a chain mediating role in the relationship between physical activity and high school students’ negative emotions, with a mediating effect value of −0.303 and an effect proportion of 25%.ConclusionOur results show that physical activity can reduce the level of negative emotions of high school students and enhance their social competence and interpersonal relationships, thus alleviating their negative emotions.